2001
DOI: 10.1007/s002440010278
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Distribution of Three PCB Congeners and Endosulfan by Developing White Leghorn Chicken Embryos (Gallus domesticus)

Abstract: The distributions of PCB 105, 156, 189, and endosulfan in incubating, maternally exposed, viable white leghorn chicken eggs (Gallus domesticus) were investigated. Hens were subcutaneously injected every 4 days with a mixture of the above chemicals. One group of five eggs was removed from the incubator at each of 9, 14, and 19 days of incubation; dissected into three compartments (embryo, chorioallantoic membrane, and yolk + albumin); weighed; frozen; and then later analyzed for the dosing chemicals. Through 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 2 publications
4
23
0
Order By: Relevance
“…Liver and brain are important target organs for some of the adverse effects induced by PCBs, but to our knowledge, PCB accumulation in these tissues was not investigated in earlier uptake studies [10,11]. Liver and brain are important target organs for some of the adverse effects induced by PCBs, but to our knowledge, PCB accumulation in these tissues was not investigated in earlier uptake studies [10,11].…”
Section: Introductionmentioning
confidence: 93%
“…Liver and brain are important target organs for some of the adverse effects induced by PCBs, but to our knowledge, PCB accumulation in these tissues was not investigated in earlier uptake studies [10,11]. Liver and brain are important target organs for some of the adverse effects induced by PCBs, but to our knowledge, PCB accumulation in these tissues was not investigated in earlier uptake studies [10,11].…”
Section: Introductionmentioning
confidence: 93%
“…As observed in laboratory studies using yolk injections and feeding trials, PCBs readily transfer in the first 70 to 85% of development [60,62]. This would more closely resemble the condition in wild birds, where more than half of the maternally deposited PCB burden is still present in the yolk at hatch [65][66][67][68].…”
Section: Discussionmentioning
confidence: 88%
“…Because PCBs are highly lipophilic and largely present in the lipid-based yolk in environmentally exposed birds, natural transfer to the embryo via yolk absorption is slow during the first 70 to 85% of development, as observed by de Roode and van den Brink [60] following yolk or air cell injections and also dietary administration [61][62][63]. In wild birds, more than half of the maternally deposited PCB burden is still present in the in the yolk at hatch [64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…Verreault et al (2006) reported that more heavily chlorinated PCBs tended to be retained in maternal tissues of the glaucous gull (Larus hyperboreus). Similarly, maternal transfer of PCBs from chicken hens to eggs is related to the degree of chlorination (Bargar et al, 2001).…”
Section: Discussionmentioning
confidence: 99%